Implikasi Ketiadaan Guru Pendamping Terhadap Perkembangan Emosional Anak Usia Dini di PAUD - Siti A Bidjuni; Nurainun Pandju; Sri A Onde; Wayan Indriani; Davina S Maladjai (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Early childhood education (ECE)serves as a faodational stage in a child’s cognitive, social, and emotional develotmet. Assistant teachers play a pivotal role in facilitating effective and conducive learning environments. They contribute to planning, impelenting, and evaluating educational activities tailored to children’s devlomental stages. However, limitations in staffing-often resultin in a single teacher managing 15 children-can impede the effectiveness of instruction and emotional support. This study underscores the positive impact of assistan teachers on classroom dynamics, including enhanced emotional stability among children, improved time management, and optimized learning autcomes. Therefore, the presence of assistant teachers is essential in fostering holistic growth and development in early childhood settings